2021
DOI: 10.2196/25351
|View full text |Cite
|
Sign up to set email alerts
|

Live Video Adaptations to a Mind-Body Activity Program for Chronic Pain and Cognitive Decline: Protocol for the Virtual Active Brains Study

Abstract: Background Chronic pain (CP) and cognitive decline (CD) are costly, challenging to treat, prevalent among older adults, and worsen each other over time. We are iteratively developing Active Brains-Fitbit (AB-F), a live video program for older adults with CP and CD that teaches mind-body skills and gradual increases in step count. AB-F has demonstrated feasibility; acceptability; and signs of improvement in emotional, physical, and cognitive functions when delivered in person to older adults. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 81 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…The Montreal Cognitive Assessment [ 13 ], a measure we previously used in our in-person study [ 14 ], has been adapted and validated for remote administration over live videoconferencing [ 15 , 16 ]. Accordingly, we developed a standardized protocol for applying the Montreal Cognitive Assessment audiovisual procedures, including mailing participants a paper with items that required drawing and instructing them to display the paper to the camera for us to screenshot over videoconferencing [ 17 ]. Our literature review also identified a validated, free-of-charge mobile app that uses GPS coordinates to measure the distance walked in 6 minutes to replace the 6-minute walk test (6MWT) [ 18 ] that we had previously conducted in our in-person study [ 14 ].…”
Section: Strategies For Remote Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Montreal Cognitive Assessment [ 13 ], a measure we previously used in our in-person study [ 14 ], has been adapted and validated for remote administration over live videoconferencing [ 15 , 16 ]. Accordingly, we developed a standardized protocol for applying the Montreal Cognitive Assessment audiovisual procedures, including mailing participants a paper with items that required drawing and instructing them to display the paper to the camera for us to screenshot over videoconferencing [ 17 ]. Our literature review also identified a validated, free-of-charge mobile app that uses GPS coordinates to measure the distance walked in 6 minutes to replace the 6-minute walk test (6MWT) [ 18 ] that we had previously conducted in our in-person study [ 14 ].…”
Section: Strategies For Remote Data Collectionmentioning
confidence: 99%
“…Our literature review also identified a validated, free-of-charge mobile app that uses GPS coordinates to measure the distance walked in 6 minutes to replace the 6-minute walk test (6MWT) [ 18 ] that we had previously conducted in our in-person study [ 14 ]. Before using the app with participants, we piloted the app and developed a standardized protocol to assist participants in downloading the app, using the app, and reporting the results [ 17 ].…”
Section: Strategies For Remote Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each open pilot, we aim to optimize the feasibility and acceptability of NF-Web and explore the quantitative outcomes. We hypothesize that the final iteration of NF-Web will meet the a priori set feasibility and acceptability benchmarks [ 8 - 10 ]. We also hypothesize that participation in NF-Web will be associated with improvement in quantitative outcomes from baseline to posttest.…”
Section: Introductionmentioning
confidence: 99%